Preparation and Characterization of Bio-Nanocomposites Film of Chitosan and Montmorillonite Incorporated with Ginger Essential Oil and Its Application in Chilled Beef Preservation - Zhang, Yin-Ping (Antibiotics (Basel), 2021)
In this study, bio-nanocomposite films containing different proportions of ginger essential oil (GEO), chitosan (Ch), and montmorillonite (MMT) were prepared and characterized, and the antibacterial effect of bio-nanocomposite films on chilled beef was evaluated. Fourier transform infrared analysis showed a series of intense interactions among the components of the bio-nanocomposite films. The infiltration of GEO increased the thickness of the film, reduced the tensile strength of the film, and increased the percentage of breaking elongation and the water vapor permeability. The migration of phenols in the films began to increase exponentially and reached equilibrium at about 48 h. The bio-nanocomposite films (Ch +0.5% GEO group, and Ch + MMT + 0.5% GEO group) effectively delayed the rise of pH, hue angle, and moisture values of chilled beef with time and slowed down the lipid oxidation and the growth of surface microorganisms on chilled beef. Altogether, the prepared biological nanocomposites can be used as promising materials to replace commercial and non-degradable plastic films.